2019
DOI: 10.3389/fvets.2019.00257
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Perspectives on Antimicrobial Use in Livestock: A Mixed-Methods Study of UK Pig Farmers

Abstract: Increasing levels of antimicrobial resistance in human and veterinary medicine have raised concerns over the irresponsible use of antimicrobials. The role of administering antimicrobials in food producing animals most frequently falls to the farmer, therefore it is essential that their use of antimicrobials is both optimal and responsible. This study sought in-depth information on the drivers behind antimicrobial use behaviors and farmer attitudes to responsible use using a mixed-methodological approach. Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…The low use of third‐generation cephalosporins and fluoroquinolones may be why only 55 per cent of farmers were aware of CIAs, and even fewer could name one. A slightly higher proportion (60 per cent) of UK pig farmers were aware of CIAs 13. Although beef farmers seem to be low users of CIAs, it is still important to improve the awareness levels in case their veterinarian prescribes them CIAs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The low use of third‐generation cephalosporins and fluoroquinolones may be why only 55 per cent of farmers were aware of CIAs, and even fewer could name one. A slightly higher proportion (60 per cent) of UK pig farmers were aware of CIAs 13. Although beef farmers seem to be low users of CIAs, it is still important to improve the awareness levels in case their veterinarian prescribes them CIAs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions among animals, humans, and the environment have also strengthened the spreading of ARB (Cheng et al, 2013;Laxminarayan et al, 2013;Maertens et al, 2019). These factors not only affect the effectiveness of prevention and treatment of animal diseases but also may endanger public safety (Coyne et al, 2016(Coyne et al, , 2019. Therefore, alternatives to antibiotics have become the spotlights of research in recent years (Lammie and Hughes, 2016;Moravej et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…In a later mixed-methods study with UK pig farmers [30], Coyne et al concluded that influences were complex, but that reduced AM use was associated with good management practices, low stocking densities and good animal health. The high cost of AMs could be a driver to reduce usage for farmers, but this was offset by improvements in pig health.…”
Section: Psychological Studies On Amr In Food-producing Animalsmentioning
confidence: 99%
“…The high cost of AMs could be a driver to reduce usage for farmers, but this was offset by improvements in pig health. Vaccination was also viewed as a feasible alternative to AM use by the majority of farmers, but few quoted concerns about AMR as a driver to reducing AM use [30].…”
Section: Psychological Studies On Amr In Food-producing Animalsmentioning
confidence: 99%